Powering Gen Z at work: the psycap–performance link and the generational twist - Sipon, Zuraidah; Majid, Muhammad; Sahari, Norshahniza; Djajanti, Atik; Marsono, A. Dewantoro (UiTM Cawangan Johor, 2025)
The performance of the workforce is crucial in determining what makes an organisation stand out. Despite the current increase in enthusiasm for Psychological Capital (PsyCap) as an innovative method for enhancing employee job performance, this research domain has garnered minimal focus concerning Generation Z (Gen Z). The prevalence of stress and anxiety among Gen Z, the youngest employment group, raises numerous issues regarding their work performance. Despite comprehensive discourse in recent research, comprehending their influence on Gen Z's work performance and the fundamental mechanisms remains constrained. This empirical study investigates the impact of Gen Z's traits on the connection between PsyCap and work performance. A purposive sampling method was employed, and primary data were collected from 167 Gen Z employees in the banking sector across Malaysia using a self-administered questionnaire. The data was subsequently analysed via Smart PLS 4.0, and it was found that the direct effect was supported while the indirect effect was not supported. The findings contribute to the theory and practice by understanding generational traits as the fundamental mechanism.